The concept of Intermarium from the Russian perspective. Outline of the topic - Kaszuba, Malina (Przegląd Wschodnioeuropejski, 2025)
The Intermarium concept is constantly employed in political and media discourse concerning Poland. Despite its active use, there has been several different definition since its introduction by J. Piłsudski. In this study, a brief analysis of the Intermarium concepts was presented, as seen in different historical periods from different perspectives. In addition, newly formed narratives in connection with the Russian-Ukrainian war, Russian-American changed relations and the Russia-NATO confrontation placed this concept in the centre of Russian political propaganda. As research material, Russian media and political scholars reflecting on the consequences of possible implementation of the Intermarium concept were considered. The work was conducted applying contextual analysis and the theory of political realism.